Application of The Problem-Based Learning Model Towards Students' Concept Understanding Level Using The Six-Tier Diagnostic Test Based on Multirepresentation - Syifaul Aini Mulyadi; S. Ida Kholida; Arin Wildani; Siddhartha Shekhar Biswas (JIPI (Jurnal IPA & Pembelajaran IPA), 2026)
Students often experience difficulties in understanding physics concepts, particularly on the topic of heat and heat transfer. These difficulties may lead to misconceptions and low conceptual understanding. Therefore, this study aimed to analyze the effect of the problem-based learning (PBL) model on students' conceptual understanding using a multirepresentation-based six-tier diagnostic test. The study employed a quantitative approach with a pretest–posttest one-group design involving students of class XI A5 at SMAN 2 Pamekasan in the 2025/2026 academic year. The research instrument was a multirepresentation-based six-tier diagnostic test (STDT) used to identify students' levels of conceptual understanding. The posttest results indicated that 83.75% of students were categorized as understanding the concept, 10.42% as not understanding the concept, and 5.83% as experiencing misconceptions. Furthermore, the paired-sample t-test revealed a significant difference between pretest and posttest scores (p < 0.05), with an N-gain score of 0.71, categorized as high. These findings suggest that the implementation of the PBL model supported by a multirepresentation-based six-tier diagnostic test is effective in improving students' conceptual understanding of physics